2014
DOI: 10.4236/ojf.2014.45056
|View full text |Cite
|
Sign up to set email alerts
|

Identification of Potential Areas for Establishment of Plantations of <i>Agave lechuguilla</i> Torr. in Coahuila, Mexico

Abstract: Adverse weather conditions and intensive use for fiber production have caused decline of natural populations of Agave lechuguilla. By these reasons, it is important to develop a sustainable management of this specie to avoid this situation. One of the first steps is to establish forest plantations as an alternative to restore A. lechuguilla habitat and increase its range while at the same time indirectly reducing erosion rates. The aim of this study was to identify the potential areas for establishment of plan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 3 publications
0
4
0
1
Order By: Relevance
“…Using the same variables, plus slope, aspect and records of the presence of the species, some authors [ 32 , 33 ] have generated zones of productive potential in this region of the country, estimating between 9 and 5 million ha that are ideal for A . lechuguilla plantations, mainly in zone 2 of our study ( Fig 1B ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Using the same variables, plus slope, aspect and records of the presence of the species, some authors [ 32 , 33 ] have generated zones of productive potential in this region of the country, estimating between 9 and 5 million ha that are ideal for A . lechuguilla plantations, mainly in zone 2 of our study ( Fig 1B ).…”
Section: Resultsmentioning
confidence: 99%
“…The results of the PCA showed that components 1 (64.17%) and 2 (25.89%) explain 90.07% of the variance. The contribution of each variable in component 1 was 29.98% (Bio 1), 27.61% (altitude), 21.80% (Bio 6), 17.95% (Bio 5), 2.66% (Bio 12) (Fig 1A) Using the same variables, plus slope, aspect and records of the presence of the species, some authors [32,33] have generated zones of productive potential in this region of the country, estimating between 9 and 5 million ha that are ideal for A. lechuguilla plantations, mainly in zone 2 of our study (Fig 1B). Flores et al [26] constructed models to estimate aboveground biomass of this species, considering the state boundaries (Fig 1 ) as the dummy variable (or zone) and found differences in biomass among the zones.…”
Section: Bioclimatic Zoningmentioning
confidence: 98%
“…is another wild species that grows in the arid and semi-arid zones of Mexico, mainly in the North part of Mexico [104]. This species is becoming of interest for establishing crops to produce fibers and bioethanol [105,106].…”
Section: Biofuels Bioenergy and Byproducts From Agave Speciesmentioning
confidence: 99%
“…Los Sistemas de Información Geográfica (SIG) representan una herramienta para explicar y hacer frente a los principales problemas como la deforestación y el cambio de uso del suelo; los resultados que se obtienen mediante su implementación son básicos para la toma de decisiones de una manera eficaz en la planeación del uso de suelo con fines de conservación, protección y/o restauración de ecosistemas degradados. Los sistemas de Información Geográfica han sido empleados en estudios de potencial productivo para el establecimiento de plantaciones en diferentes ecosistemas desde áridos y semiáridos, tropicales y bosques templados entre los que destacan los realizados por Meza, 2001;Meza, 2003;Sotelo et al, 2005;Chacón et al, 2010;Sáenz et al, 2010;Castillo et al, 2014;Muñoz et al, 2016a;Muñoz et al, 2016b. El objetivo de este trabajo fue determinar areas potenciales para establecer sistemas silvopastoriles con Pinus devoniana Lind. y Chloris gayana Kunth o Eragrostis curvula (Schard.)…”
Section: Forest Ecosystems In Michoacán Present Different Degreesunclassified
“…The results obtained for their implementation are basic for efficient decision making on the planning of land use for conservation, protection and/or restoration of degraded ecosystems. The Geographic Information systems have been used in studies of productive potential for the establishment of plantations in different ecosystems from arid and semi-arid, tropical and temperate forests (Meza, 2001;Meza, 2003;Sotelo et al, 2005;Chacón et al, 2010;Sáenz et al, 2010;Castillo et al, 2014, Muñoz et al, 2016aMuñoz et al, 2016b). (García, 1981).…”
Section: Forest Ecosystems In Michoacán Present Different Degreesmentioning
confidence: 99%